Anti-PD-1 therapy activates tumoricidic properties of NKT cells and contributes to the overall deceleration of tumor progression in a model of murine mammary carcinoma - Jovanović, Marina; Gajović, Nevena; Jurišević, Milena; Sekulić, Sofija; Arsenijević, Nebojša; Jocić, Miodrag; Jovanović, Milan; Lukić, Ružica; Jovanović, Ivana; Radovanović, Dragče (Vojnosanitetski pregled, 2022)
Background/Aim. Immune checkpoint therapy is a well-established therapeutic approach in the treatment of malignant diseases and is thought to be mostly based on facilitating the adaptive immune response. However, the cells of the innate immune response, such as natural killer T (NKT) cells, might also be important for a successful anti-programmed cell death protein-1 (anti-PD-1) therapy, as they initiate  the antitumor immune response. The aim of this study was to investigate the influence of anti-PD-1 therapy on the immune response against tumors. Methods. For tumor induction, 4T1 cells synergic to BALB/c background were used, after which mice underwent anti-PD-1 treatment. After the mice were sacrificed, NKT cells, dendritic cells (DCs), and macrophages derived from spleen and primary tumor tissue were analyzed using flow cytometry. Results. Anti-PD-1 therapy enhanced the expression of activating molecules CD69, NKp46, and NKG2D in NKT cells of the tumor and spleen. This therapy activated NKT cells directly and indirectly via DCs. Activated NKT cells acquired tumoricidic properties directly, by secreting perforin, and indirectly by stimulating M1 macrophages polarization. Conclusion. Anti-PD-1 therapy activates changes in DCs and macrophages of primary tumor tissue towards protumoricidic activity. Since anti-PD-1 therapy induces significant changes in NKT cells, DCs, and macrophages, the efficacy of the overall antitumor response is increased and has significantly decelerated tumor growth.
Keywords: antineoplastic agents; breast neoplasms; immunomodulation; killer cell, natural; macrophages; mice.